Correction: Epidemiology and Clinical Features of Patients with Visceral Leishmaniasis Treated by an MSF Clinic in Bakool Region, Somalia, 2004-2006. - Marie-Eve Raguenaud; Anna Jansson; Veerle Vanlerberghe; Gert Van der Auwera; Stijn Deborggraeve; Jean-Claude Dujardin; Ioannis Orfanos; Tony Reid; Marleen Boelaert (Public Library of Science (PLoS), 2021)
[This corrects the article DOI: 10.1371/journal.pntd.0000085.].